O trabalho de dispensação de medicamentos em uma Unidade Básica de Saúde de Belo Horizonte: um estudo da gestão e da atividade de trabalho - Luciana Souza D'avila (2009)
The Brazilian health system (SUS) implantation brought a lot of measures trying to improve the pharmaceutical assistance. The specific management policy on the field is based on resolutions, standards, concepts and research development. International agen